2020
DOI: 10.1097/md.0000000000022767
|View full text |Cite
|
Sign up to set email alerts
|

Chinese herbal medicine Wutou decoction for knee osteoarthritis

Abstract: Background: Knee osteoarthritis (KOA) causes joint pain and limited mobility, which affects the quality of life. The use of Chinese herbal medicine to treat KOA has achieved certain effects, and Wutou decoction (WTD) is one of them. But there is no high-level evidence to support this result. The purpose of this work is to evaluate WTD's efficacy and safety in the management of KOA. Methods: We will search articles in 7 electronic databases including Chinese National Kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The WOMAC sub-scales assess the dimensions of pain, functionality, and joint stiffness using 24 questions (rated 0-100 on a VAS). It has been subjected to numerous validation studies and was successfully used in the pilot study [19] and in dose-optimization studies [35] . The minimal clinically signi cant difference in the total WOMAC score has been reported to be a 12% or 16% improvement from baseline [36] .…”
Section: Outcome Measures 271 Primary Outcome Measurementioning
confidence: 99%
See 1 more Smart Citation
“…The WOMAC sub-scales assess the dimensions of pain, functionality, and joint stiffness using 24 questions (rated 0-100 on a VAS). It has been subjected to numerous validation studies and was successfully used in the pilot study [19] and in dose-optimization studies [35] . The minimal clinically signi cant difference in the total WOMAC score has been reported to be a 12% or 16% improvement from baseline [36] .…”
Section: Outcome Measures 271 Primary Outcome Measurementioning
confidence: 99%
“…KOA belongs to the category of "Impediment disease" in traditional Chinese medicine (TCM), and the comprehensive treatment of TCM using this modality has certain advantages [18][19] . Basic research has shown that TCMs affect the function of chondrocytes, protect their structure, inhibit matrix-degrading enzymes, reduce the concentrations of pro-in ammatory factors in the knee joint, and inhibit synovial in ammation, thereby alleviating joint pain and improving function [20][21][22][23] .…”
mentioning
confidence: 99%
“…Knee pain is due to liver and kidney impairment caused by cold and dampness [ 16 ]. The symptoms of joint pain described in the classic literature are consistent with KOA symptoms, including knee swelling [ 17 , 18 ]. The application of acupuncture has a long clinical history in the treatment of bone diseases [ 19 ].…”
Section: Introductionmentioning
confidence: 95%